Схема возбуждения электромагнита синхротрона на 1,5 Гэв - Ивашин В. В.; Кузнецов В. М.; Кочегуров В. А. Владимир Александрович; Ларина Н. П.; Чучалин И. П. Иван Петрович (1966, 1966)
В фонде НТБ ТПУ отсутствует